1998
DOI: 10.1007/s002130050714
|View full text |Cite
|
Sign up to set email alerts
|

Ecstasy (MDMA) effects upon mood and cognition: before, during and after a Saturday night dance

Abstract: Three groups of young people (aged 19-30 years) were compared: 15 regular ecstasy users who had taken MDMA (3,4-methylenedioxymethamphetamine) on ten or more occasions; 15 novice ecstasy users who had taken MDMA on fewer than ten previous occasions; and 15 controls who had never taken MDMA. Each subject completed a cognitive test and mood scale battery four times: an initial drug-free baseline, at a Saturday night dance/club (on-drug), then 2 days later, and 7 days later. On the Saturday night, regular ecstasy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
266
3
9

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(298 citation statements)
references
References 27 publications
(73 reference statements)
20
266
3
9
Order By: Relevance
“…However, by way of mitigation, it is noteworthy that most of the published studies that have probed cognitive deficits among ecstasy users have not resorted to urine, hair, or saliva testing (e.g., Fox et al, 2002;Morgan, 1998;Morgan, 1999;Parrott & Lasky, 1998;Rodgers, 2000). The importance of not over generalising from the present findings must also be stressed.…”
Section: Resultsmentioning
confidence: 82%
“…However, by way of mitigation, it is noteworthy that most of the published studies that have probed cognitive deficits among ecstasy users have not resorted to urine, hair, or saliva testing (e.g., Fox et al, 2002;Morgan, 1998;Morgan, 1999;Parrott & Lasky, 1998;Rodgers, 2000). The importance of not over generalising from the present findings must also be stressed.…”
Section: Resultsmentioning
confidence: 82%
“…The lasting functional effects of MDMA use may be relatively specific to mnemonic processing, since a number of studies have reported that MDMA users who are impaired on memory tasks exhibit normal performance on tests of reaction time, vigilance or selective attention (Krystal et al 1992;Vollenweider et al 1998). Additional evidence suggests that the degree of memory impairment in the MDMA user is positively correlated with the number of cumulative exposures to MDMA (Bolla et al 1998;Parrott and Lasky 1998). Finally, recent studies have demonstrated that electroencephalographic and metabolic (PET) measures of brain function are altered in MDMA users (Dafters et al 1999; …”
mentioning
confidence: 99%
“…Braida et al (2002) found no effect of MDMA on acute short-term memory in rats, but subacute memory was affected (see also Barrionuevo et al, 2000). In human studies, MDMA users have demonstrated verbal memory impairments both while on-drug (Parrott and Lasky, 1998; and after a history of ecstasy use, while other cognitive functions appeared normal (Bolla et al, 1998;Reneman et al, 2000). Recently, however, attention has been drawn to the important distinctions between effects in human adults and adolescents (Jacobsen et al, 2004), and to the realization that many studies of human ecstasy users have not controlled sufficiently for poly-drug use (Roiser and Sahakian, 2003).…”
Section: Introductionmentioning
confidence: 94%
“…It is typically taken by young people at dance parties for its effects of euphoria, increased energy, sensuality, and a feeling of closeness to others (Downing, 1986;Verheyden et al, 2003). Elation, however, is often accompanied by anxiety and confusion (Tancer and Johanson, 2003), and other undesirable side effects include minor appetite loss, dryness of mouth, and bruxism, plus a characteristic period of depression, irritability, and impaired concentration lasting several days, which begins a day or two after taking the drug (Parrott and Lasky, 1998;Verheyden et al, 2003).…”
Section: Introductionmentioning
confidence: 99%